Transient stability enhancement using optimized PI tuning of static synchronous series compensator in wind power conversion system - Ramalingegowda, Chethan Hiremarali; Rudramoorthy, Mageshvaran (Frontiers in Energy Research, 2023)
Power systems are expanding comprehensively with the increase in load demand both from residential and industrial usage. Renewable energy is penetrating into the power system to satisfy the power needs of the excessive load demand. With its potential to generate power and compensate for a large portion of the load demand, Wind Generators contribute a major chunk of renewable power to the power system. Power oscillations inherent in wind generator integration with the grid are a power quality issue to be addressed. Oscillation damping using FACTS devices is a relevant solution for the power quality issue. This paper develops the optimally tuned Static Synchronous Series Compensator (SSSC) in the wind-integrated grid system to dampen the oscillation. Teacher and Learner Algorithm (TLBO) and Gray Wolf Optimization (GWO) are used to tunning the PI controller to improve the damping response. The proposed controller’s damping performance is found to be enhanced compared to traditional controllers.